Stability of the mobile-capital Harris-Todaro model: some further results - Neary, J (Blackwell Publishing, 1988)
A necessary and sufficient condition for stability is derived for the mobile-capital Harris-Todaro model of rural-to-urban migration in developing countries when land is a scarce factor in agriculture. The stability condition when land is ignored - that the urban sector (comprising manufacturing industry and the urban unemployed) be more capital abundant - is no longer either necessary or sufficient for stability. Nevertheless, this condition always enhances stability and it is sufficient (though not necessary) for stability in many circumstances (e.g. when land is separable in production from labour and capital). Intuitive explanations of these conditions are provided.